Physiologic and metabolic effects of a suspension training workout - Dudgeon, W. D.; Herron, J. M.; Aartun, J. A.; Thomas, D. D.; Kelley, E. P.; Scheett, T. P. (International Journal of Sports Science, 2015)
Suspension training is a combination of unique training movements aimed at improving strength, endurance, coordination, flexibility, power, and core stability within a single workout. Suspension training is marketed as a cardiovascular and resistance training exercise modality performed like a circuit-training workout, in which a series of exercises are performed in rotation with minimal rest time. Objective: The purpose of this study was to determine the effects of a suspension training workout on physiologic and metabolic markers of intensity and performance. Methods: Twelve male subjects (22.0 ± 0.7 years) participated in a 60-minute whole body interval-based suspension training workout while connected to a metabolic cart. Lactate was measured before, at mid point, and various times following exercise. Results: The average heart rate (HR) during the work out was 69±2 % of estimated max. Blood lactate levels rose to 8.0±0.5 mmol/L at mid point, and remained elevated during the work out. The caloric expenditure was 340.9±13.6 kcals, or 5.3±0.4 kcal/min with a respiratory exchange ratio1.03±0.01. Conclusions: These data indicate that a suspension training workout with a 30 sec: 60 sec work to rest ratio provides at least a moderate-intensity cardiovascular workout while some data suggest a higher intensity workout is achieved.